United council of modern frustrations - Liew, Marilyn Pei Jun (2017)
The United Council of Modern Frustrations has been set up in response to the growing cries for an antidote to fix our broken world. Their solution? Four separate micro-utopias that each eradicate a particular affliction that is shared and universal among humankind; the frustration of inadequacy, heartbreak, conformity, and the lack of money. And with that, the option to live in a true state of happiness, free from life's difficulties has become an option available to all.